The agrocenotic resistance of different winter wheat varieties to weed infestation under the conditions of the Steppe zone of Ukraine - V. Matyukha; O. Tsyliuryk; S. Semenov (Карантин і захист рослин)
Goal. To identify winter wheat varieties of different maturity groups that exhibit agrocenotic resistance to weeds, based on modern resistant cultivars.